Body size, female reproduction and sexual dimorphism in the lizard Ameiva ameiva (Teiidae) in a restinga of southeastern Brazil - Rocha,Carlos Frederico Duarte (2008)
In this study 57 specimens of the lizard Ameiva ameiva (Linnaeus, 1758) collected in the restinga at Barra de Maricá, in the state of Rio de Janeiro, southeastern Brazil, were analyzed to investigate size relations and reproduction (in females) and sexual dimorphism of this population. We answered the following questions: 1) what is the minimum reproductive body size in females? 2) what is the average clutch size and 3) how is clutch size related to body size? 4) Are body and head sizes sexually dimorphic? Mean clutch size was 6.7 ± 2.1 eggs and was positively correlated with female body size. Sexual dimorphism favoring males was found: adult mean snout-vent length was great in males (124.2 ± 17.8 mm) than females (96.5 ± 23.1 mm SVL), and males were larger with respect to head width and length, and body mass. Thus, despite the marked seasonality at Barra de Maricá, A. ameiva has an extended reproductive period. Also, intrasexual selection may have acted on females to produce larger clutches, and on males, favoring larger males.